This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
3 x 2 + 5 x + 8 = a , 3 x 2 + 5 x + 1 = b
a − b = 7
( a − b ) ( a + b ) = 7
a + b = 7
a − b = 1
2 a = 8
3 x 2 + 5 x + 8 = 4
3 x 2 + 5 x − 8 = 0
( x − 1 ) ( 3 x + 8 ) = 0
Log in to reply
Can you explain how a − b = 7 ? It is given that a − b = 1 . I think radical sign must be removed in the assumption.
Wow excellent solution.
Did in the same way. Upvoted.
Problem Loading...
Note Loading...
Set Loading...
Let 3 x 2 + 5 x + 1 = a .Thus , the equation becomes:
a + 7 − a = 1
Squaring both the sides gives us:
a + 7 − 2 a ( a + 7 ) + x = 1
2 a + 6 = 2 a ( a + 7 )
a + 3 = a ( a + 7 )
Squaring both the sides:
a 2 + 6 a + 9 = a 2 + 7 a
⇒ a = 9
Hence , 3 x 2 + 5 x + 1 = 9
3 x 2 + 5 x − 8 = 0
( x − 1 ) ( 3 x + 8 ) = 0
Thus , x = ( 1 , 3 − 8 ) where , x 1 = 1 , x 2 = 3 − 8
Therefore , x 1 − 9 x 2 = 1 + 2 4 = 2 5